Vertical Disintegration in the European Electricity Sector: Empirical Evidence on Lost Synergies - Gugler, Klaus; Liebensteiner, Mario; Schmitt, Stephan (International Journal of Industrial Organization, 2017)
The EU has been promoting unbundling of the transmission grid from other stages of the electricity supply chain with the aim of fostering competition in the upstream stage of electricity generation. At present, ownership unbundling is the predominant form of unbundling in Europe. From a policy perspective, a successful unbundling regime would require that the benefits of increased competition in power generation would at least offset the associated efficiency losses from vertical divestiture. Since evidence on this topic is scarce, this study helps fill this void by empirically estimating the magnitude of economies of vertical integration (EVI) between electricity generation and transmission based on a quadratic cost function. For this purpose we employ unique firm-level panel data of European electricity utilities. Our results confirm the presence of substantial EVI of 14% for the median sized integrated utility. Moreover, EVI tend to increase with firm siz
Keywords: Cost function Economies of vertical integration Ownership unbundling Asset specificity Market complexity Electricity